Um estudo sobre a estratégia de expansão de uma escola bilíngüe - Ribeiro, Claudia Regina Nadaes (2007)
The present Study of Case has an objective to describe the development of the Project for the opening of a new unit of a bilingual educational organization in the west zone of Rio de Janeiro. The study of case shows the reasons for the growth of the bilingual educational institutions, growth of the west zone and the decision of the opening of a new unit of the School in question in this specific area. The School in study solicited for its identity to be maintained undisclosed. It opted for the realization of a study of case to describe the development of the project, in a systemized way, through a bibliography and documental research. The limitation of this case is based on the fact of being a single study case. This project can be generalized for other projects within the same institution or replicated to other educational institutions, even if it¿s not bilingual.